Treating the addicted: Cure and care service center (CCSC) in the East Coast of Malaysia - Mohd Amir Izuddin, Mohamad Ghazali; Zuraina, Ali; Anita, Abdul Rani (Universiti Malaysia Pahang, 2019)
The issue of drug misuse in Malaysia has been a complex issue in the country for more than decades. Many prevention methods have been implemented by the government in order to curb the problem. Besides that, a number of rehabilitation centers are established in treating drug addiction problem among the drug addicts. In Malaysia, a Cure and Care Service Center (CCSC) is established around the nation in hope to provide facility for the drug addicts to cure their addiction. With regards to that, the study sets out to investigate the categories of people that are admitted to CCSC and the programmes that are organized by the center for the drug addicts as well as for the community. Through qualitative approach, an interview protocol and documents; module and brochures were employed as the instruments in the current study. The findings revealed that CCSC accepted individual with drug addiction issue who intends to be treated as well as those who were caught by the authority. CCSC conducted programmes not only for the drug addicts but also for the community. Significantly, the study revealed the action that is taken by the government in tackling the drug addiction problem in Malaysia.